O índice de geodiversidade do estado de Goiás e Distrito Federal: uma avaliação sobre as unidades de conservação - Pinto Filho, Ricardo de Faria (2019)
Geodiversity represents the abiotic characteristics that make up the planet Earth. In addition to being responsible for characterizing the physical aspects of the terrestrial globe, geodiversity assumes a role as provider of ecosystem services, thus guaranteeing the management and quality of life on the planet. The thesis aims to evaluate the influence of geodiversity on the location of conservation units, highlighting the application in the State and National Parks of the state of Goiás and the Federal District. In order to fulfill the proposed objective, a method was developed to quantitatively evaluate the geodiversity, resulting in a quantitative index of the state of Goiás and the Federal District. In addition to the index, the survey carried out consultation in all the official documents of creation of the parks to analyze the influence of the geodiversity in the design of these units. The work concludes that the Geodiversity Index does not interfere in the creation and location of Park Conservation Units, but the complete work that the National and State Parks in the state of Goiás and Federal District are concerned with protecting the ecosystem services promoted by geodiversity. The work also concludes that the Geodiversity Index together with state inventories of geodiversity elements can be useful to indicate priority areas for conservation.